2022
DOI: 10.1177/01466216221108130
|View full text |Cite
|
Sign up to set email alerts
|

Two New Models for Item Preknowledge

Abstract: To evaluate preknowledge detection methods, researchers often conduct simulation studies in which they use models to generate the data. In this article, we propose two new models to represent item preknowledge. Contrary to existing models, we allow the impact of preknowledge to vary across persons and items in order to better represent situations that are encountered in practice. We use three real data sets to evaluate the fit of the new models with respect to two types of preknowledge: items only, and items a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus, EWP responding to extremely difficult items were expected to select the (incorrect) keyed response with a probability of 0.9, whereas EWP responding to extremely easy items were expected to select the (incorrect) keyed response with a probability of 0.5. This probability was conditioned on item easiness rather than examinee ability because previous research has shown that when the answer key is disclosed, items tend to represent the dominant source of variability (Gorney & Wollack, 2022b).…”
Section: Data Generationmentioning
confidence: 99%
“…Thus, EWP responding to extremely difficult items were expected to select the (incorrect) keyed response with a probability of 0.9, whereas EWP responding to extremely easy items were expected to select the (incorrect) keyed response with a probability of 0.5. This probability was conditioned on item easiness rather than examinee ability because previous research has shown that when the answer key is disclosed, items tend to represent the dominant source of variability (Gorney & Wollack, 2022b).…”
Section: Data Generationmentioning
confidence: 99%
“…preknowledge exponent preknowledge slope models of Gorney and Wollack (2022b). The probability of answering a contaminated item correctly was modified such that P * (X i = 1| ) = P(X i = 1| ) 0.1 , and the mean of the log RT distribution was modified such that M * i ( ) = M i ( ) × 0.…”
Section: Design and Analysismentioning
confidence: 99%
“…After simulating the uncontaminated data (using the procedure of Study 1), the item score and RT distributions were modified to reflect aberrant behaviour. To simulate preknowledge, we applied the preknowledge exponent and preknowledge slope models of Gorney and Wollack (2022b). The probability of answering a contaminated item correctly was modified such that Pfalse(Xi=1false|θfalse)=Pfalse(Xi=1false|θfalse)0.1, and the mean of the log RT distribution was modified such that Mifalse(τfalse)=Mifalse(τfalse)prefix×0.75.…”
Section: Simulation Studiesmentioning
confidence: 99%